PENGARUH LATIHAN SPLIT SQUAT JUMP TERHADAP PENINGKATAN KECEPATAN TENDANGAN LURUS PADA ATLET PERGURUAN PENCAK SILAT PERSAUDARAAN SETIA HATI TERATE - Syamsul Arifin; Wahyudin Nur (Lambung Mangkurat University, 2014)
Effect of Exercise Split Squat Jump Kick Against Increased Speed Straight In Athletes Pencak Silat Persaudaraan Setia Hati Terate (PSHT) Banjarmasin. The purpose of this study was to determine whether there is the effect of exercise Split Squat Jump to the increased speed straight kick in martial arts college athletes Persaudaraan Setia Hati Terate (PSHT) Banjarmasin.The method used in this study was a quasi-experimental method (Quasi- Experimental Reaserch). Design or design of the study using the one-group pretest- posttest design. Measurements were taken before and after treatment was given. Treatment effect is measured from the difference between the initial measurement / pretest (Y1) and the final measurement / posttest (Y2).The population in this study is the Athlete Pencak Silat Pencak Silat Persaudaraan Setia Hati Terate (PSHT) Banjarmasin, amounting to 35 people, and that the research samples are athletes who never played and often follow the practice amounted to 10 people with technical considerations porposif sampling or sample.Based on the conclusion of the study showed that: There was an increase in the speed of a straight kick in martial arts college athletes Brotherhood Terate Setia Hati (PSHT) Banjarmasin. Keywords: Split squat jump, speed martial arts kick straight